The effect of the quantization of the centrifugal stretching on the analysis of the rotational spectra of even-even nuclei - Mohd KH.M, Abu El Shaikh; Abdurahim, Okhunov; Hasan, Abu Kassim; Leong, Yoon Tiem (UKM, 2022)
An approach based on the idea that the spinning nucleus is stretched out along the symmetry axis under the influence of some of the centrifugal force has been proposed. The stretching in this work is treated within the framework of quantum mechanics rather than classical mechanics which had been used by Diamond Stephens and Swiatecki. Our approach led to a new formula that describes the dependence of the moment of inertia on the angular momentum. This formula is applied for the calculation of rotational ground state bands of eve–even nuclei in the atomic mass range and that have energy ratios in the range between . The results show an overall agreement with the experimental data up to high level energies. There are a small and systematic deviation appears at . This deviation increases with the increasing in and also differs from one nucleus to another.